PENINGKATAN KEMAMPUAN MENULIS KREATIF PUISI DENGAN MENGGUNAKAN MODEL PEMBELAJARAN KREATIF, KONTEKSTUAL, DAN RELIGIUS - Suryani, Sri (Universitas Tanjungpura, 2018)
Increasedability to writecreative poemsusing creative model of learning, contextual, andreligious (TRC) in the seventh grade studentsof MTs Negeri 2A Pontianakconductedto determine the applicationthat is implemented in the classroomlearning. This studyaimed to describethe planning, execution, and learning outcomes. The method usedis descriptive method, the form of qualitative research, and the type of research is classroom action research (CAR). The data were taken using tests andnon-test instruments. Data collectiontool used. Was the observation sheet and achievement test. Data were analysed qualitatively and quantitatively. Based on this research,the TRC model of learning can improve student learning out comes in creative writing poetry. The average results of student learningin the first cycle was 69.65 or at 41.38%, the second cycle increased to73.79 or at 72.41%, while the third cycle increased to78.20 or at 89.66%. Similarly, the attitudes of studentsin the following study very well increase.